Blinded and unblinded hypohydration similarly impair cycling time trial performance in the heat in trained cyclists - Funnell, M. P.; Mears, S. A.; Bergin-Taylor, K.; James, L. J. (Journal of Applied Physiology, 2019)
Knowledge of hydration status may contribute to hypohydration-induced exercise performance decrements; therefore, this study compared blinded and unblinded hypohydration on cycling performance. Fourteen trained, nonheat-acclimated cyclists (age: 25 ± 5 yr; Vo2peak: 63.3 ± 4.7 ml·kg-1·min-1; cycling experience: 6 ± 3 yr) were pair matched to blinded (B) or unblinded (UB) groups. After familiarization, subjects completed euhydrated (B-EUH; UB-EUH) and hypohydrated (B-HYP; UB-HYP) trials in the heat (31°C); 120-min cycling preload (50% Wpeak) and a time trial (~15 min). During the preload of all trials, 0.2 ml water·kg body mass-1 was ingested every 10 min, with additional water provided during EUH trials to match sweat losses. To blind the B group, a nasogastric tube was inserted in both trials and used to provide water in B-EUH. The preload induced similar (P = 0.895) changes in body mass between groups (B-EUH: -0.6 ± 0.5%; B-HYP: -3.0 ± 0.5%; UB-EUH: -0.5 ± 0.3%; UB-HYP -3.0 ± 0.3%). All variables responded similarly between B and UB groups (P >= 0.558), except thirst (P = 0.004). Changes typical of hypohydration (increased heart rate, rating of perceived exertion, gastrointestinal temperature, serum osmolality and thirst, and decreased plasma volume; P <= 0.017) were apparent in HYP by 120 min. Time trial performance was similar between groups (P = 0.710) and slower (P <= 0.013) with HYP for B (B-EUH: 903 ± 89 s; B-HYP: 1,008 ± 121 s; -11.4%) and UB (UB-EUH: 874 ± 108 s; UB-HYP: 967 ± 170 s; -10.1%). Hypohydration of ~3% body mass impairs time trial performance in the heat, regardless of knowledge of hydration status. NEW & NOTEWORTHY This study demonstrates, for the first time, that knowledge of hydration status does not exacerbate the negative performance consequences of hypohydration when hypohydration is equivalent to ~3% body mass. This is pivotal for the interpretation of the many previous studies that have not blinded subjects to their hydration status and suggests that these previous studies are not likely to be confounded by the overtness of the methods used to induce hypohydration.